2018
DOI: 10.1159/000488495
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Glaucoma: A Review

Abstract: Background: Glaucoma is the leading cause of irreversible blindness worldwide. Several techniques exist for the diagnosis and follow-up of patients. Optical coherence tomography (OCT) angiography (OCTA) is a recently developed technique that provides a quantitative assessment of the microcirculation of the retina and choroid in a fast, noninvasive way. Despite it being a novel technique, several publications have already been done in the glaucoma field. However, a summary of findings is currently lacking. Aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 70 publications
5
101
0
3
Order By: Relevance
“…Recently, the VD of RPC obtained by OCTA has emerged as a marker of microvascular disturbances associated with optic nerve damage. 8 In the present study, we investigated the superficial capillary density of three defined areas within and around the optic disc in patients with unilateral PPG and in subjects without ocular pathology. As expected, PPG eyes had on average larger C/D area, thinner RNFL and GCC than their fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the VD of RPC obtained by OCTA has emerged as a marker of microvascular disturbances associated with optic nerve damage. 8 In the present study, we investigated the superficial capillary density of three defined areas within and around the optic disc in patients with unilateral PPG and in subjects without ocular pathology. As expected, PPG eyes had on average larger C/D area, thinner RNFL and GCC than their fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of the radial peripapillary capillaries (RPC) density can be delivered with high repeatability and reproducibility. 8 The RPC network 9 has recently emerged as a promising area in glaucoma diagnosis, management and research. Many investigators showed that OCTA parameters as vessel density or blood flow index of the RPC were reduced in glaucomatous eyes compared with normal eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Hier sind weitere Studien mit größeren Kollektiven vor allem auch im Verlauf erforderlich. In einer Literaturübersicht der bis Juli 2017 publizierten Arbeiten zur OCT-A fanden van Melkebeke et al [4 ]jedoch eine bessere Korrelation der OCT-A mit funktionellen Parametern als mit der OCT und eine mindestens entsprechende Power zur Diagnosestellung.…”
Section: Transfer In Die Praxis Von Prof Dr Karl Rohrschneider (Heiunclassified
“…However, in which vascular parameters had better diagnostic ability for glaucoma and the comparison with the structural parameters, the results were varied due to many limitations. [11,[19][20][21][22][23][24][25][26] And little studies compared these parameters between glaucoma patients with normal IOP (normal tension glaucoma (NTG)) and those with high IOP(>21mmHg).…”
Section: Introductionmentioning
confidence: 99%